The impact of nanoparticles-modified repair resin on denture repairs: a systematic review - Mohammed M. Gad; Ahmad M. Al-Thobity (Elsevier, 2021)
This study aimed to evaluate the effect of nanoparticles on the mechanical properties of acrylic denture repairs. The review was designed following PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analysis) guidelines. Database search was conducted involving articles published from 2000 to 2020 using the following keywords: PMMA/nanoparticles, denture repair/nanoparticles, and repair strength/nanoparticles. PubMed/MEDLINE, Embase, Google Scholar, Scopus, and EBSCOhost were used to find only those studies used repair resin reinforced with nanoparticles for denture repairs. Due to variations between nanoparticles types, sizes, and testing properties, the quantitative statistical meta-analysis couldn't be conducted. Therefore, a descriptive data analysis was applied. Out of 379 articles, 8 articles were included; three nanoparticles, zirconium oxide (nano-ZrO2), silicon oxide (nano-SiO2), and aluminum oxide (nano-Al2O3) nanoparticles were used as reinforcements to repair resin. Seven studies investigated the effects of 0.25-7.5 wt.% nano-ZrO2 on the mechanical properties of repaired denture bases and reported positive effects with high concentrations. Two studies study investigated 0.25-0.75 wt% nano-SiO2 and found that low % nano-SiO2 concentrations improved repair strength while, one study showed that 1 and 1.5 wt.% nano-Al2O3 increased the flexural strength. Although nanoparticles offer positive effects on the properties of denture repair, inadequate studies exist. Therefore, further investigations are required.Scientific field of dental Science: Prosthodontics.